Schooling, Literacy, Numeracy and Labor Market Success - Barry R. Chiswick; Yew Liang Lee; Paul W. Miller (Institute for the Study of Labor (IZA), 2002)
This paper uses data from the 1996 Australian Survey of Aspects of Literacy to examine the effects on labour market outcomes of literacy, numeracy and educational attainment. The survey includes a range of literacy and numeracy variables that are highly inter-correlated. A ?general to specific? approach identifies the most relevant literacy and numeracy variables. Including the others adds little explanatory power. Among males and females separately about half of the total effect of education on labour force participation and on unemployment can be attributed to literacy and numeracy (the indirect effect) and about half to the direct effect of education. There is apparently no indirect effect of labour market experience through literacy and numeracy on participation or unemployment. The direct and total effects of experience are the same. The findings suggest that education is a value added process in which skills, including literacy and numeracy, are improved and that these skills enhance labour market outcomes.
Keywords: I21; J31; 330; Human capital; schooling; literacy; numeracy; earnings screening; Australia; Arbeitslosigkeit; Analphabetismus; Bildungsniveau; Erwerbstätigkeit; Schätzung; Australien